2014
DOI: 10.1055/s-0034-1383133
|View full text |Cite
|
Sign up to set email alerts
|

Die komplette mesokolische Exzision beim rechtsseitigen Kolonkarzinom – welche Rolle spielen die zentralen Lymphknoten?

Abstract: CME with CVL in right-sided colon adenocarcinoma increases the probability of complete removal of the local lymph node drainage and thus local metastatic lymph nodes. Considering this result an improvement of long-term survival by the CME procedure seems conceivable but needs to be confirmed by the current multicentre trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…A complete lymph node count was performed in all patients with malignant disease, but not in the three patients who were found to have adenomas postoperatively. Specimens from the UFA group were compared with a historic control group derived from a pilot study for the aforementioned trail [6] in which the same parameters were evaluated by the same pathologist.…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…A complete lymph node count was performed in all patients with malignant disease, but not in the three patients who were found to have adenomas postoperatively. Specimens from the UFA group were compared with a historic control group derived from a pilot study for the aforementioned trail [6] in which the same parameters were evaluated by the same pathologist.…”
Section: Patientsmentioning
confidence: 99%
“…In addition, it has been shown that the area of mesocolon removed en-bloc together with the colon and the tumor, as well as the integrity of the dissection planes, influences prognosis after curative resection. It has also been shown that the risk of lymph node metastasis is approximately 5 % in the area of the surgical trunk; this is still about 25 % of the risk to the nodes in other locations of the specimen [6]. Therefore, although not yet evaluated in a randomized trial, the current evidence points to a survival benefit regarding CME for colon cancer surgery.…”
mentioning
confidence: 97%
“…Therefore, Hohenberger coined the term “Complete Mesocolic Excision” (CME) [ 2 ]. TME results in a higher number of resected lymph nodes with a corresponding reduction of recurrence rates [ 3 , 4 ]. The evidence from cohort analyses on the oncological effects of CME [ 5 , 6 ] have resulted in the CME concept becoming a standard in many centers, including the right hemicolectomy surgery.…”
mentioning
confidence: 99%